PCSK9/LDLR System and Rheumatoid Arthritis-Related Atherosclerosis - Arida, Aikaterini; Legaki, Aigli-Ioanna; Kravvariti, Evrydiki; Protogerou, Athanasios; Sfikakis, Petros P.; Chatzigeorgiou, Antonios (Frontiers in Cardiovascular Medicine, 2021)
Background/Aims: Rheumatoid arthritis (RA) is associated with the emergence of cardiovascular disease, while chronic inflammation is considered a common denominator for their parallel progression. The Proprotein convertase subtilisin/kexin type 9 (PCSK9)/LDL-Receptor (LDLR) system is of high importance during atherogenesis, via regulating the clearance of LDL from the circulation; nevertheless the role of this molecular mechanism during RA-related atheromatosis is not known. Methods: Herein, high-resolution ultrasound measurements for arterial hypertrophy, atheromatosis and arterial stiffness as well as comprehensive biochemical profiling were performed in 85 RA patients. The circulating levels of PCSK9 and LDLR were measured and their potential associations as well as of the PCSK9/LDLR ratio with patients' characteristics and the degree of atherosclerosis were investigated. Results: Increased LDLR levels and decreased PCSK9/LDLR ratio were found in RA patients with at least 2 atheromatic plaques as compared to the ones without any plaques. In addition the levels of both PCSK9 and LDLR were positively correlated with the presence of atheromatic plaques as an age- and gender- adjusted multivariate analysis revealed. Conclusions: Our data imply that the PCSK9/LDLR system plays a significant role during RA-related atherosclerosis and may therefore be used as a screening tool for disease progression in the future.